Keintelektualan Masyarakat Johor: Tradisi Persuratan Merentas Zaman: The Intellectual of Johor Community: The Tradition of Literature Across the Ages - Nordin, Mardiana (Journal of Al-Tamaddun, 2022)
The sultanate of Johor emerged as a maritime trade civilization, centred along the Johor River around the 16th and 17th century CE. Its administrative centre shifted to the Riau-Lingga islands in the next century, and returned to the mainland state of Johor in the late 19th century. Between the 16th and 18th centuries, the sultanate of Johor emerged as a great Malay empire, a respected political entity and centre of international trade. However, these aspects should be seen as moving in line with the intellectual apogee of the Johor people. Therefore, the objective of this article is to prove that throughout the 16th and 18th centuries, the sultanate of Johor also became a centre of development of literature, language and culture. Many intellectuals emerged in Johor. The second objective is to discuss the multi-genre literary scene in Johor. Beginning with the two great Malay works, Sulalatus Salatin by Tun Sri Lanang and the Hikayat Hang Tuah, the Johor intelligentsia produced various literary works (history, literature, language, religion, statecraft, fiction, and so on) in the following centuries. Respected members of the intelligentsia produced greatly intellectual works, such as Raja Haji Ahmad, Raja Ali Haji, Raja Khalid Hitam, Raja Ali Kelana, Muhammad Ibrahim Munshi, Muhammad Salleh Perang, Muhammad Said Sulaiman and many others. This paper focuses on writtings and intellectuality in fields of history, literature and language. This study uses the qualitative method in history, especially focusing on library research. This study proves that Johor society is highly prolific in the flowering of literary and intellectual activities. This situation was also in line with the development of printing and associational activities, thus providing the intellectuality of Johor throughout time.